The development of industrial parks in Siberia: problems and solutions - K. V. Nefatova (Омский научный вестник: Серия "Общество. История. Современность")
The article is devoted to the study of the development of industrial parks in Siberia, the identification of problems and the development of proposals in this area. The terms «industrial park», «greenfield», «brownfield» are formulated, comparative analysis of the industrial parks of Siberian Federal District was carried out in the article. The specific features of industrial parks of Siberia are revealed, such as their rather pronounced social orientation, including due to the increase in their workplaces, and their predominant universality. The main problems formulated on the example of SWOT analysis of the industrial and logistics park of Novosibirsk region are ineffective promotion of the industrial and logistics park services, its negative image, difficulties in attracting labor, the need for investment, lack of resources and capacity, additional development costs, etc. The comprehensive strategy resulting from SWOT analysis, based on diversification by target segments, territory, rapid growth and active marketing policy, will ensure the achievement of economic efficiency and social significance